2007
DOI: 10.1007/s00213-006-0668-9
|View full text |Cite
|
Sign up to set email alerts
|

Effort-related functions of nucleus accumbens dopamine and associated forebrain circuits

Abstract: Along with prefrontal cortex and the amygdala, nucleus accumbens is a component of the brain circuitry regulating effort-related functions. Studies of the brain systems regulating effort-based processes may have implications for understanding drug abuse, as well as energy-related disorders such as psychomotor slowing, fatigue, or anergia in depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

66
821
3
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 888 publications
(904 citation statements)
references
References 265 publications
(333 reference statements)
66
821
3
14
Order By: Relevance
“…This challenge is difficult because a rewarding stimulus or event will elicit many or all of these reward components simultaneously and so activate many brain systems at the same time. Careful studies are needed to tease apart whether activity in a particular brain region belongs most to the 'liking', 'wanting', or learning sub-components of reward and to understand how components are assembled by larger limbic circuits into an integrated reward system (Baldo and Kelley 2007;Balleine and Killcross 2006;Beaver et al 2006;Burke et al 2008;Di Chiara and Bassareo 2007;Evans et al 2006;Everitt and Robbins 2005;Izard 2007; Koob and Le Moal 2006;Kringelbach 2004;Leyton et al 2005;Panksepp 2007;Salamone et al 2007;Schultz 2006;Volkow et al 2006;Wise 2006). …”
Section: Multiple Psychological Components Of Rewardmentioning
confidence: 99%
See 2 more Smart Citations
“…This challenge is difficult because a rewarding stimulus or event will elicit many or all of these reward components simultaneously and so activate many brain systems at the same time. Careful studies are needed to tease apart whether activity in a particular brain region belongs most to the 'liking', 'wanting', or learning sub-components of reward and to understand how components are assembled by larger limbic circuits into an integrated reward system (Baldo and Kelley 2007;Balleine and Killcross 2006;Beaver et al 2006;Burke et al 2008;Di Chiara and Bassareo 2007;Evans et al 2006;Everitt and Robbins 2005;Izard 2007; Koob and Le Moal 2006;Kringelbach 2004;Leyton et al 2005;Panksepp 2007;Salamone et al 2007;Schultz 2006;Volkow et al 2006;Wise 2006). …”
Section: Multiple Psychological Components Of Rewardmentioning
confidence: 99%
“…Pleasurable subjective pain relief for chronic pain in a phantom limb in a patient was causally induced by effective deep brain stimulation in the PVG/ PAG part of the brainstem. When using MEG to directly measure the concomitant changes in the rest of the brain, a significant change in power was found in the mid-anterior OFC to enhance several aspects of reward (Cardinal et al 2002;Everitt and Robbins 2005;Kelley et al 2002;Kelley et al 2005;Koob and Le Moal 2006;Kringelbach and Berridge 2008;Peciña et al 2006;Robbins and Everitt 2002;Salamone et al 2007;Shizgal et al 2001;Szczypka et al 2001), yet damage to the nucleus accumbens may only subtly impair the hedonic impact or related components of natural rewards such as food (Balleine and Killcross 1994;Parkinson et al 1999;Setlow et al 2002;Whishaw and Kornelsen 1993). Core 'liking' reactions to pleasure may be relatively difficult to abolish absolutely by a single brain lesion or drug, which may be very good in evolutionary terms.…”
Section: Pleasure Coding Versus Causalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of release on a subsecond time scale show that DA is relatively high during food-seeking [18]. DA depletion with 6-hydroxy-dopamine suggests that DA is needed for instrumental work output [19]. DA antagonists briefly increase operant responding for food, which then gradually declines, suggesting a loss of reward and not simply loss of motivation or motor impairment [20,21].…”
Section: Feeding and Satietymentioning
confidence: 99%
“…These activational aspects of motivated behavior have enormous adaptive significance because they enable organisms to overcome obstacles or work-related response costs that separate them from significant stimuli (Salamone 1991(Salamone , 1992Salamone et al 1997Salamone et al , 2003Salamone et al , 2007Salamone and Correa 2002;Van den Bos et al 2006;Walton et al 2006). Moreover, pathologies related to behavioral activation, such as psychomotor slowing, anergia, and fatigue, are recognized as critical aspects of depression and other psychiatric disorders (Tylee et al 1999;Stahl 2002;Salamone et al 2006Salamone et al , 2007. Over the past two decades, considerable research has demonstrated that nucleus accumbens DA is a critical component of the brain circuitry controlling effort-related behavioral processes (Salamone et al , 1997Phillips et al 2007;Niv et al 2007).…”
Section: Introductionmentioning
confidence: 99%